Role of Channel of Distribution for Consumer New Product Success in Nepal - Sharma, Bed Nath (Journal of Nepalese Business Studies, 2008)
This study concerns with channels used to distribute consumer new products and their role for new product success. To distribute consumer new product, distributor or wholesaler are in use. Sales trend of new product is in increasing trend. Distributor/wholesaler are satisfied with product features as well as delivery and terms and conditions of payment. Most of them are satisfied with manufacturer’s new product launching strategy. Competitive position of new product is found good. Distributor or wholesale are satisfied with manufacturer’s dealing. Distributors are playing significant role for new product success. The Journal of Nepalese Business Studies Vol. IV, No. 1 (2007) pp. 10-15